Think outside the building how advanced leaders can change the world one smart innovation at a time - Kanter, Rosabeth Moss. (New York PublicAffairs, 2020)
To address the big social and environmental issues of our day--from poverty, to race and gender disparities, to climate change--we need a different kind of leadership. Good leadership can help solve problems and guide an organization to success. Over a decade ago, Kanter cofounded and has since directed Harvard's breakthrough Advanced Leadership Initiative. In this book, she combines extraordinary stories from the business world with a pragmatic tool kit to deliver a new theory of leadership for producing significant societal change, one that begins where conventional leadership thinking ends
Includes bibliographical references and index.
Keywords: Leadership